Tensor asymmetry of π−-meson photoproduction on polarized deuterons; Bulletin of the Russian Academy of Sciences: Physics; Vol. 74, № 6 - Barkov L. M.; Gauzshtein V. V.; Dmitriev V. F.; Lazarenko B. A.; Levchuk M. I.; Loginov A. Yu.; Mishnev S. I.; Nikolenko D. M.; Osipov A. V.; Rachek I. A.; Sidorov A. A.; Stibunov V. N. Victor Nikolaevich; et al. (2010, 2010)
The tensor asymmetry of exclusive π−-meson photoproduction on polarized deuterons was investigated. The T 20 and T 22 components of the reaction analyzing power contribute to the measured asymmetry. The detector made it possible to record two outgoing protons in coincidence in the range of polar angles θ1,2 = 44° − 88° and in the momentum range p 1,2 = 350 − 700 MeV c −1. The measurements were performed at the VEPP-3 storage ring (Novosibirsk) using an internal target. The experimental results are compared with theoretical calculations